Energy and protein balances in traditional livestock systems and ranching in eastern Botswana - Ridder, N.A. de; Wagenaar, K.T. (Elsevier, 1986)
Compares energy and crude protein balances of cattle in traditional and ranching systems in eastern Botswana. Considers animal gross energy produced per unit, productivity at different stocking rates, liveweight, biological efficiency and pasture degradation & drought. Shows calculations of gross energy and crude protein requirements for maintaninance & production, and availability in pastures of the two systems.